USING TONGUE TWISTERS TO TEACH ENGLISH PRONUNCIATION TO AN INDONESIAN YOUNG ADULT LEARNER WITH FRENCH INTERFERENCE - MASFIROTUL UYUN, ROSITA (RETAIN : Journal of Research in English Language Teaching, 2014)
USING TONGUE TWISTERS TO TEACH ENGLISH PRONUNCIATION TO AN INDONESIAN YOUNG ADULT LEARNER WITH FRENCH INTERFERENCE Rosita Masfirotul Uyun English Education Study Program, Faculty of Language and Arts, Surabaya State University uyunarose92@gmail.com Dra. Theresia Kumalarini, M.Pd English Education Study Program, Faculty of Language and Arts, Surabaya State University Abstrak Seseorang belum dikatakan paham sepenuhnya tentang satu bahasa jika hanya mengerti tata bahasa dan kosakata dari bahasa tersebut tanpa mempelajari cara pengucapannya. Untuk orang-orang yang belajar Bahasa Inggris, terutama yang bahasa pertama atau keduanya bukanlah Bahasa Inggris, akan menemui kesulitan. Penelitian tentang bagaimana bahasa pertama mempengaruhi penerimaan bahasa kedua telah banyak dilakukan. Walaupun demikian, penelitian ini hanya akan membahas bagaimana tongue twisters membantu seorang siswa Indonesia, yang tata cara berbahasanya dipengaruhi oleh Bahasa Perancis, untuk belajar pengucapan Bahasa Inggris. Penelitian berdasar kasus ini dipilih karena peneliti hendak mengungkap satu aktifitas and masalah tertentu. Peneliti menggunakan wawancara, observasi tally, dan kuis berisi pertanyaan-pertanyaan. Telah terungkap dari wawancara yang diberikan kepada teman-teman siswa Indonesia tersebut bahwa sebenarnya ia telah dikelilingi oleh lingkungan yang mendukung untuk mnggunakan Bahasa Inggris, tetapi karena ia telah belajar Bahasa Perancis lebih dari Bahasa Inggris, ia berbicara Bahasa Inggris dengan pengaruh Bahasa Peranics yang kental. Hasil dari observasi tally yang digunakan selama siswa membaca tongue twisters juga menunjukkan bahwa di area segmental Bahasa Inggris ia terpengaruh oleh Bahasa Indonesia dan cukup parah oleh Bahasa Perancis dan di area supra segmental, bahasanya tercampur oleh Bahasa Perancis dan Bahasa Indonesia. Namun demikian, respon yang ditunjukkan oleh siswa terhadap tongue twisters bisa dikatakan positif. Kata Kunci: Tongue twisters, pengucapan, penerimaan bahasa kedua, siswa Indonesia, pengaruh Bahasa Perancis. Abstract It would be of no use if one could understand grammar and vocabulary of a language, but could not have the same comprehension of pronunciation. For the language learners who learn English would found difficulties, especially for their first or second languages is not English. The examination of language interference occurred because of L1 have already been conducted many times. This study, nonetheless, concerns the investigation of how tongue twister helps an Indonesian learner whose language was intervened by his foreign language, French, to learn English pronunciation. Case-based research was chosen because it was a study of particular activity and problem. To gather the data the researcher used interviews, tally observation, and questionnaires as the instruments. It was found from the interviews given to the learner’s colleagues that he was adequately surrounded by English, but because he learnt French more than English, he spoke English with heavy nasal sound. The result from tally observation which was applied when the learner read the tongue twisters aloud was a proof that in English segmental features he was interfered by Indonesian and heavily by French and in supra segmental he was probably influenced both by French and Indonesian. Despite of that interference, the response showed by the learner regarded to tongue twisters was positively fine. Keywords: Tongue twisters, pronunciation, second language acquisition, Indonesian learner, French interference. INTRODUCTION These days, English has widely used as communication tool which can link up the people from all around the world to share information. However, the fact that English is an inconsistent language which the written form is different with the spoken form makes some people are difficult to learn. Hence, the ability of recognising the meaning of the words spoken in English is required. It will be useless if one merely comprehends grammar and has extensive vocabulary, but cannot pronounce appropriately. This condition can make people misunderstand. Pronunciation, thus, is essentially needed to accomplish beneficial oral communication between speakers and the listeners. The fact, nevertheless, that English is neither the native nor second language of Indonesian makes the Indonesian language learners find some difficulties in learning pronunciation since some sounds in English do not exist in Indonesian sounds. The situation above also happens when the researcher teaches in one on one private course. The researcher finds that although the learner is Indonesian native speaker, his language is interfered by another foreign language, French. He likes to learn languages and French is one of some languages he learns and uses mostly. In this case, he does not have problem with the motivation to learn, nor the comprehension of English grammar and vocabulary. The problem appears when he is asked to pronounce some English words. As we know that some English words are similar to French in written form but not in pronunciation. It happens for many times. For example, when he read the word “Argentina”, he did not pronounces it as /?:d??n’ti:n?/ but /?:d???tin/ like he pronounced the word “wrong” /r??/. Another example is when he was asked to pronounce the word “attempt”. It should be pronounced as /?’tempt/, but he pronounced as /?’t??/. The last example that made the researcher is interested to observe him was when he spelled NYC (New York City) as /n/ /i: grek/ /si:/, not /n/ /waI/ /si:/. From the example above we know that not only the English words that are alike to French in written form, but the English words which actually do not exist in French and the spelling ends with “emp” or “ent” will be pronounced French-alike by the learner; even if the native French real problem when they learn English pronunciation is they are hardly able to pronounce the English vowel sounds (Walter; 2001). Many studies exhibiting about the native language interference in learning foreign languages have been proven, but unfortunately not many studies present about foreign language interference in teaching another foreign language. For example, Bhela (1999) indicated that there is an interference of L1 (native language) in acquiring L2 (second language) in written language form. Kaushanskaya and Marian (2009) in their study also find that L1 could interfere the learners in learning novel words of L2. In this study the researcher, however, would not try to seek for the further reasons linguistically why the learner’s pronunciation gets interfered; though later the researcher would also provide a brief description of the learner’s education background, language learning, and environment which probably can explicate linguistic cause. The intention precisely is how the researcher helps him by giving a treatment which is different to what the researcher had given to him before this research is conducted. This is not an experimental study, nonetheless, as the researcher does not attempt to see how much the improvement is showed during tongue twister is applied or what the differences which would emerge between before and after the treatment is given. Instead, the analysis results are expected to be the description of how tongue twisters work to help the learner to advance his English pronunciation and the learner’s response toward tongue twisters. Before the researcher decided to use tongue twisters, repetition activity like the learner reading a passage a loud and when he made mistake the researcher tried to model the right pronunciation and asked him to repeat it many times. It, however, did not give the learner an improvement. As a result, tongue twister is chosen. Tongue twister is a phrase or sentence which is difficult to say as it has similar repeated sounds (Baker and Goldstein, 2008). The example of tongue twister in English is “She sells seashells in the sea shore” or “Peter Piper picked a peck of pickled peppers”. Doing tongue twister should be enjoyable as we know it is hard to be pronounced undoubtedly and well even for the English native speakers. In relation with the explanations above, this research would be a case study research which is intended to reveal the details of a particular phenomenon and describe it with profound analysis, rather than confirm relationship or test hypotheses (Hancock and Algozzine, 2006). It is covered in a study of a singularity which the subject of the research is particular condition (Bassey, 1999); it is in line with the fact of why this research is conducted. Through case study, researchers hope to gain in-depth understanding of situations and meaning for those involved (Hancock and Algozzine; 2006, 11). Since case study is included in qualitative research, it needs quotes of key participants, anecdotes, prose composed from interviews, and other literary techniques to depict the real condition of the subject of the study (Hancock and Algozzine, 2006). Duff (2008) also stated that if case study is conducted in a good way, it will have a high degree of completeness, depth of analysis, and readability. Based on the background of the study, the research questions would be: How can tongue twisters help the learner to pronounce the English words? How is the learner’s response toward tongue twister? RESEARCH METHOD It was stated in the introduction that this research is a case study, the form is of which obviously descriptive qualitative. Case study was chosen since the researcher attempted to figure out the evident regarded to problem occurred in particular learner; in this case, Indonesian learner with French interference. Qualitative social scientists tend to study small samples of purposively chosen cases of a given event or process (Schrank, 2006; 21). Typically, case study researchers use various instruments such as interview, observation, and archives to draw the data together (Ary, Jacobs, Razavieh, and Sorensen, 2010). The design is, also, flexible and may change during the investigation if appropriate (Ary, et. al, 2010; 32). This research was conducted in one private course, so that there is only one respondent. Since it had only one subject, the researcher was involved as both the teacher and the observer. Therefore, in this study the use of terms “researcher” and “teacher” is same as they refer to the same person. Investigating how the tongue twisters works to help the learner to fix his English pronunciation and how he responds becomes the important matters for the researcher. To solve the matters, a procedure was prepared. Interview, tally observation, and questionnaire were employed to assist the researcher make summary and interpretation to answer the research questions. The researcher initially makes appointments with the two friends of the learner who are from the same language community with him and a friend from same university with him. The interview intends to build the assumption of the researcher’s curiosity about how much the learner know and use French in everyday life until it hinders his English pronunciation. The interview result could probably give information in line with what has occurred in the teaching and learning activity. Two meetings were also held to explain how tongue twisters facilitate the learner to pronounce English words properly. There were two weeks interlude in between two meetings with same activity in each weeks which the explanation is: First meeting (first week) In the first week, the researcher uses voice recorder to help the researcher note down the learner’s pronunciation. The learner is initially asked whether he knows tongue twisters or not. If he does not know, the explanation will be given to the learner. After that, the researcher provides a list of English tongue twisters in order to be read aloud by the learner. Second meeting (two weeks later) In the second week, before the researcher starts the lesson, she asks the learner whether he practices the tongue twisters in a week or not and if he does, what his opinion is. Then, the lesson is done exactly the same like the first meeting.. During the lesson, tally observation sheets helped the researcher to save the details of the learner performance. In order to know the learner’s response toward the use of tongue twister in correcting his pronunciation, the questionnaire was also used. Some questions regarding to the learner’s feeling of the tongue twisters and what he expects toward tongue twisters application were asked to the learner. It was accomplished before and after the two meetings were conducted. RESULTS AND DISCUSSION The presentation of the data was based on the instruments used by the researcher. The first was interview. It was conducted twice, the first was with the learner’s college friend (February 18th 2014) and the second was with the learner’s colleague from a language community (March 5th 2014). From the first meeting, it can be assumed that the learner was in fact surrounded by English as interviewee 1 told the researcher that there are two courses which the students are required to use English both spoken and written. The courses are Communication Text and English Language. She also told that some days ago he was asked by the lecturer to have a speech in English. His English was overall acceptable, but he had difficulties in finding out the most appropriate words in English. Besides, sometimes he pronounced some English words with nasal voice like French accent. It, however, still could be understood. When the researcher gave the interviewee 1 a question regarded how much the learner used English and French in campus, it could be known that the learner uses English inside the classroom and French outside the classroom. It was also explained that the learner also uses French inside classroom with a lecturer who is also able to speak French. The interviewee also told that he occasionally promoted to his friends to learn and take French course. He is eager in learning French because he wishes that someday he can go there for both studying and improving his career. This fact is told by himself to the researcher and the interviewee in different chance. The result of the interview with interviewee 2 was slightly the same with the last interview with the interviewee 1. She said that he wanted to have an occupation in France, so the first thing he did was to learn French. She also told the researcher that the learner used French more than English. If it was shown in percentage, it would be 60% for French and 40% for English. She and the interviewer are in the same mind that anything he wrote on the social media, he always used French. In some occasion the interviewee 2 found that when he spoke English, his language was influenced by French. For example, when the word “compulsion” is supposed to be pronounced as /k?m’p?l?n/, but he pronounced it as /kom’pul?o?/. In the first meeting with the learner (February 21st 2014), the researcher asked the learner whether he knew what tongue twisters are. It transpired that the learner did not know what it is. For that reason, the researcher gave him a brief explanation and example like “She sells shells on the sea shores”. After that, he read the tongue twisters while the researcher taking notes by using tally observation sheet. There were nine tongue twisters adapted from www.uebersetzung.at/twister/en.htm which they are: An exempt girl, Marienne, attempts to tempt her friend. A pleasant peasant who has a pheasant descends the stairs in unpleasant way at present. Mr. Burrier is a courier of Mr. Spurrier which is a rich furrier. The well-known Mr. Hiddleston’s clone groans as his scone is in the cone. Common action of the champion becomes a phenomenon. Eleven benevolent elephants are in heaven. Mrs. Sansom’s grandsons make fun of a nun with a gun until she runs. Mr. Buchanan misunderstands the grand command of the clan king in the land. If Kantie can tie a tie and untie a tie, why can’t I tie a tie and untie a tie like Kantie can. The result surprised the researcher since the learner made a significant progress compared to that of the very first time the learner came to the researcher. Seven of nine tongue twisters could be pronounced, even though he still read them with full of attention. It was also already explicated that the learner was difficult to pronounce the words ending “mpt” and “ent”. In this study he, nevertheless, could pass the words with the end “ent” such as “benevolent”, though he pronounced it doubtfully. The mistakes made was always the same, number 1 and number 8. In the first meeting he was mistaken in pronouncing the words “attempt”, “tempt”, and “untie”. In the next meeting (March 9th 2014) he failed to pronounce four words, the three of which were similar to the previous, and the remaining was “Marienne”; later he made a self-correction to the word “Marienne”. He again pronounced “attempt” as /?’t??/. As well as “attempt”, the word “tempt” was also articulated as /t??/. What made the researcher wonder was how he failed to pronounce “attempt” and “tempt”, while he succeed in pronouncing “exempt”. The same situation occurred when he pronounced “untie” as /?nti:/, instead of /?n’taI/. It was interesting because he could pronounce “tie” as /taI /. The learner was not only interfered by French but also his native language, Indonesian. There was a usual mistake done by Indonesians when they try to speak English. In Indonesian, sound /ð/ are replaced by sound /d/ because of the nonexistence of sound /ð/. For that reason, the learner pronounced the word the as /de/. Another problem also appeared regarded to supra segmental features. It was already known that one should learn where the stress is put in English words, unlike when one learns French. It is already set that the stress words in French are in the last syllable (Major, 2001; Walter, 2001). This fact makes English sound flat when it is spoken by French people. The absence of sounds in a language could cause difficult pronunciation for the non native speakers. The study conducted by Hashemian and Soureshjani (2011), whose the participants are Iranian EFL students from elementary, intermediate, and advanced level, showed that in the side of segmental features there were twelve sounds in English were pronounced as the other sounds and eight sounds were mispronounced. In supra segmental, the most of the participants likely misplaced the stress. The errors made by the participants were caused by their unfamiliarity of the English phonemes. The learner is indeed not French, but he read in a monotone way. The researcher, however, could not assume that his performance was affected by French because there is a probability that the Indonesian language could also influence him. Yong (2001) reported that a range of stress in Malay/ Indonesian has fewer propensities than English which cause an impression of monotony. More to the point, learners do not construct rules at their vacuum; rather they work with whatever information at their disposal (Ellis, 1997: 57). In this case, the L1 knowledge stored in their brain is also involved. The questionnaires were given two times (pre and post activity) to the learner. There were two parts in questionnaire. The first part was a checklist form with three questions in which the learner should choose from strongly agree to strongly disagree for each question. The questions were related to his opinion whether tongue twisters helped him to learn English pronunciation significantly or not. The second part was an open question form which consisting of five questions regarded to his opinion of which the easiest and the most difficult part. .The learner, generally, enjoyed the process. Although he read the tongue twisters watchfully, he never complained that the words were too difficult for him. It could be seen from the learner’s positive answers on the whole. He answered that there were five words such as “attempts”, “tempt”, “pleasant”, “pheasant”, and “peasant” as the most difficult parts. On the other hand, the words “common”, “action”, “champion”, and “phenomenon” were the easiest parts. CONCLUSIONS The tongue twisters might slow down the learner to read aloud the sentences, but it could help the learner to be accustomed to English sounds as it also involved the brain activity. In this case, however, it seemed that the learner probably did not habituate himself to it yet, so that he made the same mistakes in two meetings. For that reason, it could be concluded that tongue twisters less helpful for the learner. However, despite the unsatisfactory result, the learner showed the willingness to learn English pronunciation by using tongue twisters. REFERENCES Ary, D., Jacobs, L. C., & Sorensen, C. K. (2010) Introduction to Research in Education (8th ed.). California: Wadsworth. Baker, A. & Goldstein, S. (2008). Pronunciation Pairs: An Introduction to the Sounds of English. Cambridge: Cambridge University Press. Bassey, M. (1999). Case Study Research in Educational Settings. London: Open University Press. Bhela, B. (1999). ‘Native language interference in learning a second language: Exploratory case studies of native language interference with target language usage’. International Education Journal, 1(1), 22-31. Duff, P. A. (2008). Case Study Research in Applied Linguistics. New York: Lawrence Erlbaum Associates. Ellis, R. (1997). Second Language Acquisition. Oxford: Oxford University Press. Hancock, D. R. & Algozzine, B. (2006). Doing Case Study Research: A Practical Guide for Beginning Researchers. New York: Teachers College Press. Hashemian, M. & Souresjani K. H. (2012). ‘An analysis of pronunciation errors of Iranian EFL learners’. Iranian Journal of Research in English Language Teaching. 1(1), 5-18. Kaushanskaya, M. & Marian, V. (2009). ‘Bilingualism reduces native-language interference during novel-word learning’. Journal of Experimental Psychology: Learning, Memory, and Cognition, 35(3), 829–835. Major, R. C. (2001). Foreign Accent: The Ontogeny and Phylogeny of Second Language Phonology. New Jersey: Lawrence Erlbaum Associates, Inc. Schrank, A. (2006) ‘Case Study’ in Perecman, E. & Curran S. R. (eds.) A Handbook for Social Science Field Research: Essays & Bibliographic ources on Research Design and Methods. California: Sage Publication, Inc. Walter, C. (2001) ‘French speakers’ in Swan, M. & Smith, B. (eds.) Learner English: A Teacher’s Guide to Interference and Other Problems (2nd ed.). Cambridge: Cambridge University Press. Yong, J. Y. (2001) ‘Malay/ Indonesian speakers’ in Swan, M. & Smith, B. (eds.) Learner English: A Teacher’s Guide to Interference and Other Problems (2nd ed.). Cambridge: Cambridge University Press.